A FEW REMARKS ON THE INTRODUCTION OF THE TERM “MARKETING” INTO ECONOMIC LITERATURE - Bochenek, Mirosław (Ekonomia i Prawo. Economics and Law, 2015)
Representatives of most academic disciplines, both at home and abroad, collect theoretical concepts developed by previous generations, thus creating histories of the sciences cultivated by them. In this respect, Polish academics engaged in marketing are lagging behind. The purpose of this study is to establish the “paternity” of the term “marketing”. The authors of publications up to now have claimed that in 1912 this term, interpreted as market distribution, was introduced into the specialist literature by the American economist Arch Wilkinson Shaw. Meanwhile, after conducting studies of the literature, it has turned out that in 1890, and so 22 years earlier, the term “marketing” in the sense of introducing goods to the market was used by Alfred Marshall. So, it was this British economist who turned out to be the author of the above innovation in terminology in the field of economics.